DIMENSI LEVEL ORGANISASI PADA PENGEMBANGAN KAPASITAS DALAM PENYERAPAN TENAGA KERJA PADA UNIT LAYANAN DISABILITAS KETENAGAKERJAAN KABUPATEN BOYOLALI - Ayu Agustina; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Every citizen has an equal right to employment, including persons with disabilities. The government has established a minimum quota policy of 2% for workers with disabilities in government agencies and 1% for private companies, as well as the establishment of Employment Units (ULD) at the regional level. However, in practice, the employment rate for persons with disabilities remains relatively low, and the implementation of the ULD's duties faces various capacity constraints. Therefore, capacity development at the organizational level is a crucial aspect in increasing the effectiveness of employment for persons with disabilities. This study aims to analyze the organizational-level dimensions of capacity development in employment at the ULD Ketenagakerjaan in Boyolali Regency. This study used a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation studies. Data analysis was conducted using Grindle and Hilderbrand's capacity development theory. The results indicate that the organizational-level dimensions of capacity development at the ULD Ketenagakerjaan demonstrate adaptive and collaborative capacity through cross-actor involvement, utilization of the LaPenta digital system, and participatory work mechanisms based on needs assessments.